A Comparison of Corporate Planning Practice in American and Australian Manufacturing Companies - Capon, Noel; Christodolou, Chris; Farley, John U.; Hulbert, James (Journal of International Business Studies, 1984)
Group planning practices of leading American and Australian manufacturing firms are compared and contrasted. Despite some differences, a broad pattern of similarity emerges across many elements of the planning systems.